Utilização de compósito de fibra de vidro/resina epóxi para reforço estrutural de vigas de concreto armado - Andrade, Nathan Pereira de [UNESP] (2017)
Factors such as project and execution errors, lack of maintenance and inspection, and changes in loading cause deficiencies to reinforced concrete structures. In this sense there is the need of application of structural reinforcement systems. This study presents some of the techniques of structural reinforcement, emphasizing the manufacturing process, implementation and execution of structural reinforcement with composite material based on pre-impregnated of glass fiber fabric type plain weave 1 x 1 and epoxy resin. Beams made of steel reinforced concrete, composite material beams and hybrid (steel reinforced beams and composite beams combined together) were submitted to 4 points flexural test. Experimental and calculated results for the dimensioning of the beams were compared, allowing the validation of the calculation method and its implementation. It was possible to notice both the efficiency of the composite material applied to the reinforcement of steel/concrete beams, as well as the efficiency of the calculation models applied in this work